2021
DOI: 10.3389/fmicb.2021.749888
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics Regulate Longitudinal Plankton Community Structure in an Alpine Cascade Reservoir System

Abstract: Previous studies report significant changes on biotic communities caused by cascade reservoir construction. However, factors regulating the spatial–temporal plankton patterns in alpine cascade reservoir systems have not been fully explored. The current study explored effects of environmental factors on the longitudinal plankton patterns, through a 5-year-long study on the environmental factors and communities of phytoplankton and zooplankton in an alpine cascade reservoir system located upstream of Yellow Rive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…It is exposed to the mixing of water and bottom sediments during floods, which causes high turbidity in the water under such situations. On the other hand, the Tresna Reservoir has a purifying effect on the water of the Soła River—the purifying effect of dam reservoirs, especially cascade systems, has been described in publications from various countries [e.g., 23 , 50 ]. Stachowicz and Czernoch 31 found that the waters of the Porąbka and Czaniec reservoirs have more favorable physical and chemical parameters than the water of the Tresna Reservoir.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is exposed to the mixing of water and bottom sediments during floods, which causes high turbidity in the water under such situations. On the other hand, the Tresna Reservoir has a purifying effect on the water of the Soła River—the purifying effect of dam reservoirs, especially cascade systems, has been described in publications from various countries [e.g., 23 , 50 ]. Stachowicz and Czernoch 31 found that the waters of the Porąbka and Czaniec reservoirs have more favorable physical and chemical parameters than the water of the Tresna Reservoir.…”
Section: Resultsmentioning
confidence: 99%
“…Fragilaria crotonensis, Aulacoseira granulata, Nitzschia acicularis, Asterionella formosa, Diatoma vulgaris . These taxa have been observed in eutrophic reservoirs in various parts of the world—Finnish lakes 60 , Czech reservoirs 73 and Chinese 23 , as well as in Polish oxbow lakes rich in biogens 74 . Species with oligotrophic (e.g., Encyonema minutum ) and mesotrophic preferences (e.g., Oocystis borgei ) also appeared in small numbers.…”
Section: Resultsmentioning
confidence: 99%
“…Algae respond to these parameters, such as Anabaena and Cosmodladium related to SRP, Asterococcus and Chroococcus responding to BOD and Ceratium responding to turbidity. Previous studies report that these algae well-adapted groups and can tolerate environmental factor deficiencies more successfully than less adapted species, and the abundance of algae represents eutrophic water [35,36]. Therefore, the presence of this group is not conducive to good water quality in the dam, leading to a deterioration in water quality.…”
Section: The Relationship Between Phytoplankton and Environmental Var...mentioning
confidence: 99%